Evaluation the Result of Conservative Management in Fail Back Surgery Syndrome - Goni, Md Fahad; Acharjee, Shoumen; Ilias, Mohammad (IAHS Medical Journal, 2022)
Background: Failed back surgery syndrome is defined as persistent chronic low-back pain and/or leg pain lasting more than 1 year, despite of one or more surgical procedures. Instrumented spinal fusion has been offered by surgeons as a potential treatment to recover from pain and functional disability. Good outcome of instrumented spinal fusion cannot be ensured by treating surgeon. Thus, patient don’t want to go for second surgery conservative management may be the only hope here. This study here to evaluate the recovery and functional status of patients afterconservative management of failed back surgery syndrome. Evaluate the neurological and functional outcome of conservative treatment of failed back surgery syndrome. Establish the conservative management as a treatment protocol so that patient can avoid economical and psychological trauma of a second surgery. Materials and methods: After proper consent from patient and attendant this prospective interventional study was - carried out in the Department of Orthopaedics and Spine Surgery Unit, Bangabandhu Memorial Hospital (BBMH) Chattogram for last 1 years. Within this period total 10 failed back surgery syndrome patients were treated in OPD. Patient underwent surgery in other hospital in the city. All are treated by conservative management in the form of rest, analgesic and some exercise. All patients evaluated before and after treatment clinically with the help of using Visual Analog Score (VAS) of back pain, Modified Macnab criteria, Oswestry Disability Index (ODI) by Oswestry Low Back Pain Disability Questionnaire. Results : Total 20 patient were taken with FBSS among them 80% were female. After conservative management - there is significant recovery of neurological (Sensory) symptoms in early follow-up. Functional outcome measuring pre & post treatment VAS & ODI, Waddel index showed significant improvement in patient after treatment. Overall functional outcome most of the case 14(70%) had excellent, 4 (20%) case had poor for whom second surgery may recommended. Conclusion: Failure of back surgery has remained a challenging condition to treat for any surgeon. During primary surgery surgeons should be more careful regarding case selection. Second surgery is always more cumbersome, conservative management can play a satisfactory role here. IAHS Medical Journal Vol 4(1), June 2021; 9-12